Evaluation of the Changes associated with Bone-Anchored Pendulum Appliance after the Completion of Comprehensive Orthodontic Treatment - Beyza Hancıoğlu-Kırcelli; Zafer Özgür Pektaş; Sevinç Karan; Ömür Polatözsoy (Galenos Yayinevi, 2008)
The aim of this clinical study is to evaluate the effects ofthe bone-achored pendulum appliance (BAPA) during and after the comprehensive orthodontic treatment. The sample for the evaluation of bone-anchored pendulum appliance (BAPA) consisted of 11 consecutively treated Class II orthodontic patients (10 female, 1 male; mean age, 13 ± 2.1 years). A conventional pendulum appliance was modified to obtain anchorage from an intraosseous screw instead of the premolars. Screws were placed in the anterior paramedian region of the median palatal suture. Skeletal and dental changes were measured on cephalograms, and dental casts were obtained before (T1), after distalization (T2), and after comprehensive orthodontic treatment (T3). Nonparametric Wilcoxon sign rank test was used for comparison of paired values of the measurements. A super Class I molar relationship was achieved in a mean period of 7.5 ± 1.9 months. The maxillary first molars distalized an average of 4.6 ± 2.2 mm (p=.005) in the region of the dental crown by tipping distally an average of 13.0 ± 4.1 mm (p=.003). Comprehensive orthodontic treatment was completed in an average time of 24,5 ± 5,5 months. At the end of T3, the maxillary first molars moved mesially an average of 2.8 ± 2.6 mm (p=.014) and tipped mesially 15.8 ± 7.6° (p=.003). Besides, there was statistically a significant increase Co-Pog and B-PTV distances from T2 to T3 of 1.6 ± 1.4 mm (p=.017) and 0.9 ± 1.1 mm (p=.027), respectively. Also, lower first molar was detected to move mesially an average of 1.5 ± 1.1 mm (p=.007). Since all of the patients' comprehensive treatment ended with Class I molar and canine relationship maintenance of the Class I relationship can be attributed to the anterior growth of the mandible and dentoalveolar compensation mechanism. BAPA can be considered as an alternative method for the correction of Class II malocclusion especially in borderline cases that requires nonextraction treatment.